Analisis Kelayakan Pengembangan Proyek Citra Garden Puri Semanan Citra Garden City - Anugrahenny Sekreningtyas (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
Jakarta is experiencing a tremendous residential growth due to the high level of urban migration to Indonesia’s capital. Therefore, PT CD, through its subsidiary, PT CAP, tries to fulfill the increasing demand of residential housing by developing a 180,328 m2 of land in the West of Jakarta. The development is called the Citra Garden Puri project.This paper is developed to determine the feasibility of the project through cash flow sensitivity analysis. There are 3 (three) assumptions used, which are : the normal, pessimistic, and optimistic assumptions. These assumptions are tested through 3 (three) calculation methods: Payback Period, Net Present Value (NPV), Internal Rate of Return (IRR), and Profitability Index (PI).  The results of the sensitivity analysis are are Based on the Payback Period calculation, the project is deemed feasible. The current company’s payback period is approximately 4 years, while the payback periods for the project are 24 months, 24 months, a for the normal, and optimistic assumptions consecutively. Based on the NPV calculation, the project is deemed feasible. The NPV is positive for all assumptions. Based on the IRR calculation, the project is deemed feasible. The IRR for the normal and optimistic assumptions are higher than the Weighted Average Cost of Capital (WACC). Therefore, based on the results of the sensitivity analysis of the project’s cash flow, it is concluded that the Citra Garden Puri Semanan project is a profitable business decision. To increase profitability level, the company should try to find other financing alternatives to lower the cost of capital.